Analisa Kinerja Penerapan Standard Protokol Keamanan IEEE 802.11 Pada Layanan Wireless Fidelity - Kalam, M Zatiar Erwan; Wirastuti, Ni Made Ary Esta Dewi; Widyantara, I Made Oka (Majalah Ilmiah Teknologi Elektro; Vol 20 No 1 (2021): (Januari - Juni ) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2021.v20i01.P10, 2021)
Communication network depends on the WLAN , and there is so much demand on the Quality Of Service (QoS) WLAN like Throughput , delay , and filter to secure the Communication Data , therefore a network security mechanism is using the Wired Equivalent Privacy (WEP), WiFi Protected Access (WPA), and WPA2 [14]. Mall Bali Galleria has several alternative for free WiFi, There is so many Wi-Fi has been installed causing the problem interference, and that affect the performance of the WiFi, MBG has the Indoor and Outdoor Area, The alternative to handle the interference is to using the automation channel by implementing Channel Fly , Background Scanning and Static Channel.  From the security mechanism, Channel And Frequencies made by doing scenario on every single access point to get the best scenario , from the scenario that has been submitted The best score of the packet loss on indoor area Scenario that uses 4 AP with the 5Ghz Frequency , static channel , WEP-64 is 0,016ms of the packet loss , the Outdoor areas scenario that uses 5 AP with 5Ghz frequency ,Channel Fly , WEP-64 get 0,094ms of the packet loss , The best jitter score for the indoor area that uses 2 AP , 5Ghz Background Scanning , WPA 2 is 1.336ms of the jitter, outdoor area 8 AP , 5Ghz Frequency , static channel , WPA2-Mixed get 1,116 ms of Jitter , The Throughput best scores is indoor area with 1 AP , 5Ghz Frequency, Static Channel , WPA2-Mixed get 78,7Mbps of the Throughput, for the Outdoor Areas using 8 AP , 5Ghz Frequency , Background Scanning, Disable Security is 80Mbps Of The Throughput , if it compared with the existing scenario the performance is improved to 10-30%.  WEP has good packet loss score however it has smallest Throughput. Static channels are recommended on the location that have high interference.